Linkages between arctic and mid-latitude weather and climate - Jaiser, Ralf; Akperov, Mirseid; Timazhev, A.; Romanowsky, Erik; Handorf, Dörthe (Dr.); Mokhov, I. I. (Meteorologische Zeitschrift, 2023)
The study addresses the question, if observed changes in terms of Arctic-midlatitude linkages during winter are driven by Arctic Sea ice decline alone or if the increase of global sea surface temperatures plays an additional role. We compare atmosphere-only model experiments with ECHAM6 to ERA-Interim Reanalysis data. The model sensitivity experiment is implemented as a set of four combinations of sea ice and sea surface temperature boundary conditions. Atmospheric circulation regimes are determined and evaluated in terms of their cyclone and blocking characteristics and changes in frequency during winter. As a prerequisite, ECHAM6 reproduces general features of circulation regimes very well. Tropospheric changes induced by the change of boundary conditions are revealed and further impacts on the large-scale circulation up into the stratosphere are investigated. In early winter, the observed increase of atmospheric blocking in the region between Scandinavia and the Urals are primarily related to the changes in sea surface temperatures. During late winter, we f nd a weakened polar stratospheric vortex in the reanalysis that further impacts the troposphere. In the model sensitivity study a climatologically weakened polar vortex occurs only if sea ice is reduced and sea surface temperatures are increased together. This response is delayed compared to the reanalysis. The tropospheric response during late winter is inconclusive in the model, which is potentially related to the weak and delayed response in the stratosphere. The model experiments do not reproduce the connection between early and late winter as interpreted from the reanalysis. Potentially explaining this mismatch, we identify a discrepancy of ECHAM6 to reproduce the weakening of the stratospheric polar vortex through blocking induced upward propagation of planetary waves.